Meeting the Challenge of Cancer Survivorship in Public Health: Results from the Evaluation of the Chronic Disease Self-Management Program for Cancer Survivors - Risendal, Betsy C.; Dwyer, Andrea; Seidel, Richard W.; Lorig, Kate; Coombs, Letoynia; Ory, Marcia G. (Frontiers in Public Health, 2015)
.